THU0504 Utilisation of anti-osteoporotic drugs in real-world data: a study of gender-related differences. (12th June 2018) - Orlando, V.; Monetti, V.M.; Guerriero, F.; Russo, V.; Moretti, A.; Piscitelli, A.; Piscitelli, R.; Iolascon, G.; Menditto, E.
Abstract : Background: Osteoporosis is mostly defined as the disease of women, because the prevalence and fracture rates are much higher in postmenopausal women than in older men. However, there has been increasing recognition that male osteoporosis also represents an important burden as a common cause of morbidity, mortality and health care expenditure. Also, men are more likely than women to have osteoporosis that is undiagnosed and undertreated. Moreover, bone fracture are important factors of high mortality and morbidity rates in osteoporotic patients. Lack of persistence is common among subjects using oral anti-osteoporotic drugs, and leads to increased risk of fragility fracture. Objectives: The aim of this study is to perform gender specific analysis regarding the persistence to antiosteoporosis drugs. Methods: We conducted a retrospective cohort study using administrative data from four local health authorities in the Abruzzo Region (Central Italy), which comprise about 9 00 000 inhabitants (68% of the overall regional population). Patients 60 years of age or older were included if at least one prescription for any antiosteoporosis drugs had been filled in between January 1, 2006 and December 31, 2006. Persistence estimates over time (discontinuation rates were assessed at 365 days) were derived using Kaplan–Meier survival analysis, stratifying for gender, considering treatment discontinuation as failure event and comparing differences using Log-rank test (1 degree of freedom). Results: The final cohort consisted of a total of 7867 patients (87.2% women). The mean patient age for both genders at the index date was 74.5 years. The crude analysis of long-term gender persistence showed a significant difference between women and men: the relative number of persistence patients after 1 year was 66.4% in men and 44.7% in women. The Kaplan Meier plots of time to persistence start to differ for men vs women approximately 60 days after treatment start (figure 1). Conclusions: The results showed that gender influences adherence to therapy and this is an issue that could be taken in strong consideration in tailor intervention to improve adherence. References: [1] Cawthon PM. Gender differences in osteoporosis and fractures. Clinical Orthopaedics and Related Research2011;469(7):1900–1905. [2] Bor A, Matuz M, Gyimesi N, et al. Gender inequalities in the treatment of osteoporosis. Maturitas2015;80:162–169. [3] Christopher J, et al. Sex and gender considerations in male patients with osteoporosis. Clinical Orthopaedics and Related Research2011;469(7):1906–1912. Disclosure of Interest: None declared